Perceived Social Support as A Predictor of Perceived Stress in Nursing Students in Pakistan - Mushtaq, Rabia; Ahmad, Riaz (Pakistan Languages and Humanities Review, 2024)
The objective of present research was to study the predictive association between perceived social support and perceived stress in nursing students in Pakistan. The correlation study was conducted to find if there would be a significant predictive association between perceived social support and perceived stress in student nurses. The sample of 555 nursing students of ages 19-30 years (M= 21.41; SD=2.25) was recruited by using purposive sampling technique. Multidimensional Scale of Perceived Social Support and Perceived Stress Scale were used in Urdu language as research instruments. Descriptive statistics was used for demographic characteristics of the sample, while Regression analysis was used to analyze the predictive link between study variables. Result indicates the statistically significant predictive relationship between PSS and PS in nursing student (r=.576, p<0.001). It is recommended that social support may play a crucial role in reducing perceived stress and its adverse impacts on mental health of nursing students.